Agricultural growth in Japan, Taiwan, Korea, and the Philippines (University Press of Hawaii, 1979)
Part I: The Analysis of Agricultural Growth ; Part II: The Four Country Studies ; Part III: Measurement of Agricultural Output and Inputs...